Differential proteomic analysis of respiratory failure in peripheral blood mononuclear cells using iTRAQ technology - SUN, GUOPING (Biomed Rep, 2016)
Respiratory failure (RF) is a state in which the respiratory system fails by its gas exchange functions. Failure of the lung, which is caused by all types of lung diseases, leads to hypoxaemia with type I respiratory failure. Failure of the pump leads to hypercapnia or type II respiratory failure. Using isobaric tags for relative and absolute quantification (iTRAQ) technology to identify and quantify the total proteins in peripheral blood mononuclear cells (PBMCs) of RF patients and identify the differentially expressed proteome. The present study analyzed the total proteins in the PBMCs of RF patients and healthy controls using the eight-plex iTRAQ added with strong cation-exchange chromatography and liquid chromatography coupled with tandem mass spectrometry. The differentially expressed proteins were identified by MASCOT. A total of 4,795 differentially expressed proteins were identified, and 403 proteins were upregulated and 421 were downregulated. Among them, 4 proteins were significantly differentially expressed, which were upregulated KIAA1520 protein and γ fibrinogen type B (AA at 202) and downregulated chain A, crystal structure of recombinant human platelet factor 4 and myosin regulatory light polypeptide 9. iTRAQ technology is suitable for identifying and quantifying the proteome in the PBMCs of RF patients. The differentially expressed proteins of RF patients have been identified in the present study, and further research of the molecular mechanism of the differentially expressed proteins is required to clarify the pathogenesis and identify novel biomarkers of RF.